Government Responsibility Towards Handling Investment Conflicts In Central Java - Nazmudin Nazmudin; Mohamad Yusup; Dian AM (HK-Publishing, 2026)
Abstract The purpose of this study is to improve understanding of the importance of government responsiveness in handling investment conflicts in Central Java. To determine the efforts made by the Central Java government to improve its responsiveness in handling investment conflicts. To analyze the level of responsiveness of public complaint services regarding investment in Central Java which is experiencing a decline and is hampered by the problem of expensive land. The research method used is descriptive qualitative with an empirical field study approach. Data collection was carried out through observation, interviews, and documentation studies on the implementation of Law Number 25 of 2007 concerning Investment in Central Java. The results show that the responsiveness of the Central Java Provincial Government in resolving investment conflicts rests on the capabilities of proactive and mediative regional leadership. The escalation of land dispute conflicts was successfully reduced through a strategy of standardizing land value zoning, optimizing the Integrated Industrial Zone (KIT), and implementing an inclusive compensation scheme based on the